NEGOSIASI IDENTITAS PERAN GENDER PADA FILM BOLLYWOOD (Jurnal Komunikasi, 2022)
Patriarchal culture has long been rooted in society, regulating all aspects of life for both men and women. One of them is married life. Men and women are both required to fulfill traditional roles according to patriarchal standards. Men are demanded to be providers, while women only do domestic work. Women have careers only to support their husbands. The film Ki & Ka tries to show a different role from what is usual in society. So this film aims to explain how the dynamics of gender equality is represented in the Ki & Ka film. The theory used in this research is the Identity Negotiation Theory by Stella Ting-Toomey. This theory seeks to explore the ways in which identity is negotiated in interactions with other people, especially in various cultures. The method used is semiotic analysis, by trying to analyze the symbols that appear in this film. The results showed that Ki and Ka were able to show the dynamics of identity negotiation, such as efforts to fit in with the environment, to show self-identity and the turmoil of people around when gender equality was applied in society.